Polycaryocyte formation mediated by Sindbis virus glycoproteins. - Mann, E (1983)
The process of cell fusion mediated by Sindbis virus membrane proteins synthesized after infection was examined. At the times after infection at which virus proteins were detectable on the cell surface, Sindbis virus-infected BHK-21 cells were found to express a fusion function after brief treatment at acid pH. In studies employing wild-type virus and temperature-sensitive mutants and testing drug or protease inhibition of virus production, we made the following observations on Sindbis virus-mediated fusion from within. (i) Fusion requires the synthesis of virus glycoproteins and their transport to the cell surface. (ii) Modification of the cell plasma membrane by polypeptides PE2 and E1 alone is not sufficient for expression of the fusion function. (iii) The proteolytic conversion of plasma membrane-associated PE2 to E2 is not essential for fusion. (iv) Glycosylation of virus plasma membrane proteins is essential for fusion. (v) The lesions of Sindbis virus temperature-sensitive mutants do not affect their ability to fuse cells.